CMET-06. AN ANALYSIS OF RESPONSE ENDPOINTS FOR BRAIN METASTASIS PATIENTS TREATED WITH STEREOTACTIC RADIOSURGERY AND PD(L)-1 INHIBITORS - Kotecha, Rupesh (Neuro Oncol, 2019)
PURPOSE: Recent trials have evaluated the role of anti-PD(L)-1 inhibitors alone in patients with newly diagnosed brain metastasis, resulting in a suggested paradigm shift. In the absence of randomized comparisons, an evaluation of outcomes for similar patients treated with radiotherapy are needed to provide baseline comparative data. METHODS: This retrospective cohort study included patients diagnosed with brain metastasis from 2010–2017 at a single tertiary care institution who received SRS and at least one anti-PD(L)-1 inhibitor. Primary endpoints included the rate of best intracranial response (either a complete [CR] or partial response [PR]), rate of intracranial benefit (percentage of patients with stable disease [SD] for at least 6 months), and overall objective response rates. RESULTS: 150 patients met the eligibility criteria for this study and the median follow-up time was 10 months (Range: 1–130 months). Only a minority of patients from this cohort would have been eligible for comparative systemic therapy alone trials: 8 (CheckMate 204, CM), 8 (ABC), and 50 patients (Yale Institutional trial, YI). Best intracranial objective response rates for these trial eligible patients were 64% (CM), 64% (ABC), and 72% (YI), respectively. The 6-month rates of intracranial benefit across patients were 75% (CM), 75% (ABC), and 93% (YI), respectively. The rates of either a CR, PR, or SD across trial eligible patients were 100% (CM), 100% (ABC), and 94% (YI), respectively. More than 50% of patients experienced out-of-field progression in each of the patient subgroups. CONCLUSIONS: Over a seven year period, very few patients treated with SRS and anti-PD(L)-1 inhibitor therapy in a busy academic practice would have been eligible for systemic therapy alone per trial eligibility criteria. In these highly favorable subgroups, patients experience high rates of objective response, best intracranial response, and intracranial benefit after SRS and anti-PD(L)-1 therapy, representing optimal brain metastasis management.